Impact of straw returning on soil ecology and crop yield: A review - Vincent Ninkuu; Zhixin Liu; Aizhi Qin; Yajie Xie; Xiao Song; Xuwu Sun (Heliyon)
Several studies have demonstrated the effect of straw return on enhancing soil ecology, promoting sustainable agricultural practices, and cumulative effects on plant yield. Recent studies have focused on straw return methods and their impact on soil nutrient cycling and the overall physicochemical composition of the soil. Despite the substantial progress and successes, several research gaps in these studies require further investigations to harness the full potential of straw return. This review provides a thorough examination of straw diversity and decomposition mechanisms, the effects of straw on soil microorganisms, the interactions between cellulolytic nitrogen-fixing microbes and lignocellulose biomass, as well as nutrient mineralization, organic matter content, and their influence on plant growth and yield. This review also examined the effects of straw return on plant pathogens and its allelopathic impact on plant growth, highlighting research gaps to encourage further studies that could fully realize the potential benefits of straw return in agricultural fields for optimal plant growth.